Mesangial expansion at 5 years predicts death and death‐censored graft loss after renal transplantation. Issue 1 (24th November 2020) - Kukla, Aleksandra; Alexander, Mariam P.; Turkevi‐Nagy, Sandor; Merzkani, Massini; Park, Walter; Smith, Byron; Zhang, Pingchuan; Benavides, Xiomara; D'Costa, Matthew; Morales Alvarez, Catalina; Denic, Aleksandar; Bentall, Andrew; et al.
Abstract: Death with a functioning graft and death‐censored renal allograft failure remain major problems for which effective preventative protocols are lacking. The retrospective cohort study aimed to determine whether histologic changes on a 5‐year surveillance kidney biopsy predict adverse outcomes after transplantation in recipients who had: both Type 2 diabetes (T2DM) and obesity (BMI ≥ 30 kg/m 2 ) at the time of transplantation (T2DM/Obesity, n  = 75); neither (No T2DM/No obesity, n  = 78); No T2DM/Obesity ( n  = 41), and T2DM/No obesity ( n  = 47). On 5‐year biopsies, moderate‐to‐severe mesangial expansion was more common in the T2DM/Obesity group (Banff mm score ≥2 = 49.3%; Tervaert classification MS ≥ 2b = 26.7%) compared to the other groups ( p  < .001 for both scores). Risk factors included older age, higher BMI, HbA1C, and triglycerides at 1‐year post‐transplant. Moderate‐to‐severe mesangial expansion correlated with death with function (HR 1.74 (1.01, 2.98), p  = .045 Banff and 1.89 (1.01, 3.51) p  = .045 Tervaert) and with death‐censored graft loss (HR 3.2 (1.2, 8.8), p  = .02 Banff and HR 3.8 (1.3, 11.5), p  = .01 Tervaert) over a mean of 11.6 years of recipient follow‐up post‐transplant. These data suggest that mesangial expansion in recipients with T2DM and obesity may reflect systemic vascular injury and might be a novel biomarker to predict adverse outcomes post renal transplant.